Adolescent perspectives on addressing teenage pregnancy and sexually transmitted infections in the classroom and beyond. Issue 1 (2nd January 2020) - Fisher, Christopher M.; Kerr, Lucille; Ezer, Paulina; Kneip Pelster, Aja D.; Coleman, Jason D.; Tibbits, Melissa
ABSTRACT: Sex education both in and beyond the classroom has been shown to have the potential to ameliorate negative sexual health outcomes for adolescents. School-based sex education and sexual health services targeting young people should be informed, in part, by teenagers themselves. Semi-structured interviews were conducted with 41 young people aged 13–22 years in a mid-sized midwest US city to inform such programme development. Analysis employed both top-down and bottom-up approaches to coding. Four themes emerged regarding sex education activities in and out of school: the need for knowledge of current activities aimed at prevention; information-seeking behaviours; personal views on how to address teenage pregnancy and sexually transmitted infections (STIs); and the ideal place to address these issues. Current activities were seen as ineffective or non-existent. Many participants indicated they would not engage actively in information-seeking unless they were affected personally by the issues. Participants' suggestions of how to address the issues included improving school services, introducing media campaigns and having peer or trusted-adult educators. Participants identified the need for services that offered confidentiality, a non-judgemental approach and a comfortable space to meet. Through direct engagement with youth, this research makes recommendations for interventions to address teenage pregnancy and STIs.